(untitled) (Journal of Asian Development Studies, 2020)
This paper investigates the technical efficiency of the 29 coal mines in the eastern salt range of Punjab using parametric as well as non-parametric frontier techniques. The results show that there has been some improvement in the efficiency of the coal mines, though the magnitude of improvement remains small. By using SFA All coefficients are statistically significant except that of salaries, wood packing cost and fuel and electricity, which is insignificant. A possible explanation may be that the presence of rigidities in terms of salaried workers lay off may prevent firms from an optimal utilization of the employee input secondly wood packing chargers increased due to different mine areas because this expanse depends on the area. Similarly, due to load shedding in Pakistan cause the inefficiency in fuel and electricity cost. The results from both the approaches are consistent, and in line with similar studies. The results also shows a mixed technical efficiency scores for the coal mines. However the coal seam, age of mine manager, experience of mine manager, and qualification of mine manager have directly proportional impact on the technical efficiency of the mines. Whereas vertical depth of coal mine and length of coal mine has adverse impact on the efficiency of the coal mine.